Anti-Allergic Activity and Mast Cell Stabilization of Areal Parts of Solnum Torrvum on Experimental Animals - Ahamed, Syed Mansoor; T R, Sagar; Gowda, Sindhu; G, Chidanandamurthy; R, Nandeesh; E, Manjunatha; Kumar B S, Ashok (Journal of Neonatal Surgery, 2025)
A Solanum torvum (Solanaceae) areal part of plant has been extensively in traditional medicine for the treatment of asthma and bronchitis. The present study was designed to evaluate the anti-allergic activity of hydro- alcoholic extract of solanum torvum. Areal parts of plant in experimental animals. The ant allergic activity of the extract was evaluated on compound 48/80 induced mast cell degranulation in rat mesentery and milk induced leukocytes and eosinophilia in mice. Treatment of HAST (300 and 600 mg/kg p.o.) showed significant (p<0.001) protection against compound 48/80 (1 mg/kg s.c.)-induced mast cell degranulation mesenteric pans. The hydro alcoholic extract of S. torvum Areal parts of plant inhibited milk induced model Pre-treatment of HAST (200 and 400 mg/kg, p.o.) to group of mice exhibited significantly (p<0.001) reduced the milk (4 ml/kg s.c.)-induced elevated levels of blood total leukocyte and eosinophils counts. The observed beneficial effect of title plant may be attributed to reported bioactive compounds and their synergistic outcome.